2011
DOI: 10.1002/ange.201102527
|View full text |Cite
|
Sign up to set email alerts
|

The 3D Solution Structure of Thurincin H, a Bacteriocin with Four Sulfur to α‐Carbon Crosslinks

Abstract: Einblick ins Peptid: Für das antimikrobielle Peptid Thurincin H wurde eine Modifizierung nach der Translation vermutet. Eine MS/MS‐Sequenzierung identifizierte nun die modifizierten Reste, und NMR‐spektroskopische Studien in Lösung ergaben eine 3D‐Struktur für Thurincin H, in der vier S‐Cα‐Thioether‐Brücken auftreten (gelb im Bild). Diese Struktur könnte auch für einige andere Bacteriocine mit identischer Masse bedeutsam sein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This “sactionine” linkage is distinct from the C-S bond found in lanthipeptides, which link Cys residues to the β-carbon of dehydrated Ser/Thr residues via a Michael-like nucleophilic addition reaction (Figure 7E). 40 Five sactipeptides have been reported 39 including: subtilosin A, 27 from Bacillus subtilis 168; 41 thurincin H, 28 from B. thuringiensis SF361; 42 sporulation killing factor (SKF, 29 ) from various B. subtilis ; 43 and the two-component thuricin CD (Trn-α, 30 and Trn-β, 31 ) from Bacillus thuringiensis DPC 6431. 44,45 Herein, we discuss recent advances in our understanding of rSAM-mediated thioether bond formation during sactipeptide biosynthesis.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…This “sactionine” linkage is distinct from the C-S bond found in lanthipeptides, which link Cys residues to the β-carbon of dehydrated Ser/Thr residues via a Michael-like nucleophilic addition reaction (Figure 7E). 40 Five sactipeptides have been reported 39 including: subtilosin A, 27 from Bacillus subtilis 168; 41 thurincin H, 28 from B. thuringiensis SF361; 42 sporulation killing factor (SKF, 29 ) from various B. subtilis ; 43 and the two-component thuricin CD (Trn-α, 30 and Trn-β, 31 ) from Bacillus thuringiensis DPC 6431. 44,45 Herein, we discuss recent advances in our understanding of rSAM-mediated thioether bond formation during sactipeptide biosynthesis.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…42 Detailed structural characterization of thurincin H revealed that it contains four sactionine linkages between Cys4, Cys7, Cys10, and Cys13 to the α-carbons of Ser28, Thr25, Thr22, and Asn19, respectively. 42 The BGC is comprised of three identical copies of the 40-residue precursor peptide thnA , thnB (rSAM enzyme), thnP (protease), thnD/E/T (three-component ABC transporter), thnR (transcriptional regulator), and thnI (unknown function). Studies using purified ThnB demonstrated that it was responsible for sactionine formation.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…As elucidated by the NMR analysis, one face of the thurincin H hairpin structure is a cluster of hydrophilic amino acid residues. The other hydrophobic residues form prominent patches over the remaining surface of the peptide (Sit et al, 2011). Subtilosin A, a cyclic bacteriocin of B. subtilis, has been characterized both structurally and functionally and possesses some of the same, unique chemical features as thurincin H, including sulfur to a-carbon bonds and a net anionic charge.…”
Section: Discussionmentioning
confidence: 99%
“…The first reported representative of this RiPP class was subtilosin A [3,4], which was, alongside the sporulation killing factor (SKF) [5] found in Bacillus subtilis 168. The remaining sactipeptides originate from Bacillus thuringiensis DPC 6431 (Trn-a and Trn-b, which together form the two-component bacteriocin thuricin CD) [6,7], and from B. thuringiensis SF361 (thurincin H) [8]. Their known biological functions range from antimicrobial activities against Gram-positive bacteria for thuricin CD, thurincin H and subtilosin A to the spermicidal or hemolytic activities of certain subtilosin A variants [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%